2019
DOI: 10.1111/echo.14413
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐modality cardiac imaging in advanced chronic kidney disease

Abstract: Cardiovascular disease (CVD) is the leading cause of death worldwide and is particularly frequent among those with severe renal impairment. Early diagnosis and therapeutic intervention may help alleviate the burden of cardiovascular complication within this population. In the last years, advances have been made toward developing noninvasive imaging techniques that could offer better insight into the cardiac involvement in end‐stage renal disease (ESRD). Conventional transthoracic echocardiography remains the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…47 The use of CMR for the quantification of LVMI reduced the interobserver and intraobserver variability known from using echocardiography and provided accurate anatomic information in excellent agreement with autopsy results. 48,49 A careful evaluation of the patients' volume status throughout the trial and stratification by residual renal function in the randomization mitigated confounding of the treatment effect by volume overload. Blood pressure control was equally good in both groups.…”
Section: [3-5] 4 [3-5]mentioning
confidence: 99%
“…47 The use of CMR for the quantification of LVMI reduced the interobserver and intraobserver variability known from using echocardiography and provided accurate anatomic information in excellent agreement with autopsy results. 48,49 A careful evaluation of the patients' volume status throughout the trial and stratification by residual renal function in the randomization mitigated confounding of the treatment effect by volume overload. Blood pressure control was equally good in both groups.…”
Section: [3-5] 4 [3-5]mentioning
confidence: 99%
“…This has been reliably used in the diagnosis of cardiomyopathies, quantification of areas of fibrosis, prognostic determination, and guidance of therapies [38]. Several studies have reported increased T1 values in CKD and ESRD patients [39]. Myocardial fibrosis unrelated to ischemia occurs early in uremic cardiomyopathy, and this increases with the severity of CKD [40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exploring new biomarkers to identify high-risk CKD patients prone to CRS-4 becomes the hotspot, such as asymmetric dimethylarginine (ADMA) [ 33 ], nonoxidized parathyroid hormone (PTH) [ 34 ], sST2 and Gal-3 [ 25 ]. In addition, some noninvasive imaging plays an essential role in assessing heart and vascular abnormalities, for example multi-modality cardiac imaging [ 35 ], and cardiac magnetic resonance [ 36 ]. These techniques can assist in identifying early changes in myocardial tissue characterization [ 37 , 38 ], which can be applied as indicators for early diagnosis and risk stratification of CRS-4.…”
Section: Discussionmentioning
confidence: 99%